Inhibitory effects of type 2 diabetes serum components in P450 inhibition assays can potential diagnose asymptomatic diabetic mice. Issue 6 (December 2020) - Tamaki, Shun; Imaishi, Hiromasa
Abstract: Human cytochrome P450 (or CYP) inhibition rates were investigated in sera from high fat diet (HFD)-induced type 2 diabetes (T2D), T2D recovered, and asymptomatic mice models to verify whether P450 inhibition assays could be used for the detection of disease, evaluation of therapeutic effect, and early diagnosis of T2D. In T2D mice, the blood glucose levels markedly increased; while blood glucose levels of recovered mice exceeded 200 mg dL −1, these eventually returned to the levels seen in control mice. In asymptomatic mice fed with short term HFD (stHFD), no changes in blood glucose levels were observed. The inhibition rates of CYP1A2, CYP2A13, and CYP2C18 in T2D mice significantly increased. Whereas in recovered mice, these changes returned to the same levels noted in the control mice. Changes in the inhibition rates of CYP2A13 and CYP2C18 in stHFD mice were similar to those in T2D mice. A receiver operating characteristic (ROC) curve analysis showed high area under the ROC curve (AUC) values (0.879–1.000) of CYP2A13 and CYP2C18 in T2D and stHFD mice, indicating their high diagnostic accuracy. Collectively, this study validates the P450 inhibition assay as a method for the therapeutic evaluation and early diagnosis of T2D mouse models. Graphical abstract: Image 1